Management of patients with hypersensitivity to platinum salts and taxane in gynecological cancers: a cross-sectional study by the European Network of Young Gynaecologic Oncologists (ENYGO) - Zwimpfer, Tibor; Bilir, Esra; Gasimli, Khayal; Cokan, Andrej; Bizzarri, Nicolò; Razumova, Zoia; Kacperczyk-Bartnik, Joanna; Nikolova, Tanja; Pletnev, Andrei; Kahramanoglu, Ilker; Shushkevich, Alexander; Strojna, Aleksandra; et al. (Cancers, 2024)
Platinum and taxane chemotherapy is associated with the risk of hypersensitivity reactions (HSRs), which may require switching to less effective treatments. Desensitization to platinum and taxane HSRs can be used to complete chemotherapy according to the standard regimen. Therefore, we aimed to investigate the current management of HSRs to platinum and/or taxane chemotherapy in patients with gynecologic cancers. We conducted an online cross-sectional survey among gynecological and medical oncologists consisting of 33 questions. A total of 144 respondents completed the survey, and 133 respondents were included in the final analysis. Most participants were gynecologic oncologists (43.6%) and medical oncologists (33.8%), and 77.4% (n = 103) were involved in chemotherapy treatment. More than 73% of participants experienced >5 HSRs to platinum and taxane per year. Premedication and a new attempt with platinum or taxane chemotherapy were used in 84.8% and 92.5% of Grade 1-2 HSRs to platinum and taxane, respectively. In contrast, desensitization was used in 49.4% and 41.8% of Grade 3-4 HSRs to platinum and taxane, respectively. Most participants strongly emphasized the need to standardize the management of platinum and taxane HSRs in gynecologic cancer. Our study showed that HSRs in gynecologic cancer are common, but management is variable and the use of desensitization is low. In addition, the need for guidance on the management of platinum- and taxane-induced HSRs in gynecologic cancer was highlighted.
Gesehen am 23.08.2024